New regression models to evaluate the relationship between biomechanics of gymnastic vault and initial vault difficulty values - Atikovic, A. (Journal of Human Kinetics, 2012)
The main objective of this paper was to determine the relationship between biomechanical parameters of vault flights with respect to new models of initial vault difficulty values in men`s artistic gymnastic. The study sample included vaults (n=64) and models (n=5) from the 2009 Code of Points (CoP) of the Federation International of Gymnastics (FIG). The dependent variable included all difficulty values ranging from 2-7.2 points, while the sample of independent variables included twelve biomechanical parameters. After implementing the regression analysis, it could be established that the best model derived only the second flight phase with 95% of explained variance.